2000
DOI: 10.1164/ajrccm.162.5.9908113
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ozone on Inner-City Children with Asthma

Abstract: Within a cohort of 846 inner-city asthmatic children aged 4 to 9 yr, we looked for subgroups that were more susceptible to the effects of summer ozone. Daily diaries were compared with ambient ozone levels to evaluate effect modification by demographic and environmental characteristics. Children born > 3 wk prematurely or weighing < 5.5 lb. had greater declines in morning % peak expiratory flow rate (PEFR) (1.8% versus 0.3% per 15 ppb ozone, p < 0.05) and a higher incidence of morning symptoms (odds ratio = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 33 publications
(31 reference statements)
3
38
0
Order By: Relevance
“…Individual-level risk factors that modified the response to ozone in this cohort have been reported previously [11]. In particular, it was found that asthmatic children born prematurely (v37 weeks) or with a low birth weight (v2.5 kg) had a significantly greater response to increases in ozone.…”
supporting
confidence: 71%
“…Individual-level risk factors that modified the response to ozone in this cohort have been reported previously [11]. In particular, it was found that asthmatic children born prematurely (v37 weeks) or with a low birth weight (v2.5 kg) had a significantly greater response to increases in ozone.…”
supporting
confidence: 71%
“…Several other panel studies have examined the importance of medication use to air pollutant associations (2,(25)(26)(27). Two of these studies showed stronger associations between asthma outcomes and air pollutants among subjects taking any asthma medication versus subjects not taking asthma medication, but they did not separate subjects by anti-inflammatory medication use (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Children are considered to be more sensitive to air pollution than adults [4], and asthmatic children are particularly vulnerable to the adverse health effects of air pollution. Studies of asthmatic children have concluded that exposure to high concentrations of ozone or PM significantly enhances the risk of respiratory symptoms, asthma medication use, and reduced lung function, such as decline in peak expiratory flow or forced expiratory flow in a short time [5][6][7][8][9][10]. However, while a number of studies have been conducted in the field of air pollution epidemiology, few have examined the association between meteorological elements and asthma attack, and the adverse health effects of low-level exposure to air pollutants remain unclear.…”
Section: Introductionmentioning
confidence: 99%